'It sort of has the feel of being at home': Mixed‐methods evaluation of a pilot community‐based palliative end‐of‐life service in a regional setting. (24th June 2022) - Handley, Tonelle; Jorm, Christine; Symington, Christine; Christie, Louis; Forbes, Erin; Munro, Alice; Cheney, Richard
Abstract: Objective: To evaluate the acceptability and effectiveness of a small community‐based hospice on the end‐of‐life experiences of patients and families. Methods: Mixed‐methods study. Design: Patient admission data were used to assess utilisation of the hospice. Open‐ended interviews with hospice patients and their families/carers were used to understand the emotional effects of the service. Setting: A small palliative end‐of‐life hospice in a rural town in NSW, Australia, during a 12‐month trial period that began in March 2019. Data were collected in October–November 2019. Participants: Patients, families and carers who used the hospice during the trial period, as well as staff working at the hospice. Main outcome measure(s): Quantitative measures included the number of patients admitted to the hospice, the average length of stay and the overall occupancy rate of the hospice. Quantitative interviews were used to explore the experiences of patients and families who used the hospice, and whether the hospice met their end‐of‐life needs. Results: During the trial, 58 patients were admitted to the hospice. The majority of admissions were less than 7 days. Two patients and nine family members were interviewed about their experiences, and six staff completed interviews. Experiences were consistently positive, with the community setting of the hospice contributing to a peaceful and home‐like end‐of‐life experience. Interviewees described meaningful relationships with staff, a pleasant physical environment and the comprehensive care provided were key elements of this experience. Conclusion: This model, embedding end‐of‐life care within a residential aged care facility, facilitated a positive end‐of‐life experience for residents of this regional community. The development of local models to meet local needs is essential to enabling people nearing the end of life to remain in their location of choice, and ensure that their needs are met at this vulnerable time.